IDENTIFIKASI KEBUTUHAN PELANGGAN DALAM PERANCANGAN DAN PENGEMBANGAN KONSEP TAS BACKPACK YANG ERGONOMIS DAN MULTIFUNGSI - Nataya Charoonsri Rizani; Agie Satria (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Backpack is one of the most attractive bag because of its excellence in the load management.Preliminary research conducted in the productive age segment (17-40 years) respondents showed thatthe majority (53 percent) were dissatisfied with the existing backpack. Then narrowed the marketshare in the segment of students and white collar worker who required high mobility. Customeridentification was conducted by several questionnaires. There were 6 primary needs and 21 targetspecification which connected on needs metric matrix.